Economic Growth, Policies and Influencing Factors: The Case of Albania - Vangjeli, Eleni; Mancka, Anilla (European Journal of Economics and Business Studies, 2016)
Monetary and fiscal policies are two policies that the government could use to keep a high level of growth, with a low inflancion. Fiscal policy has its initial impact on the stock market, while monetary policy in market assets. But, given that the goods and active markets are closely interrelated, both policies, monetary as well as fiscal have impact on the economy, increasing the level of product through the reduction of interest rates. In our paper we will show how functioning monetary and fiscal policies. But also in our paper we will analyze the different factors which have affected the economic growth of the country. The focus of our study is the graphical and empirical analysis of economic growth, policies and influencing factors. For the empirical analysis we have used data on the economic growth in Albania for 1996– 2014.
Keywords: Monetary and fiscal policies, economic growth, export growth, FDI, economic indicators, Political stability